Diagnosis of Non-alcoholic fatty liver disease (Journal of Pathology of Nepal, 2016)
Non Alcoholic Fatty Liver Disease is the deposition of fat in liver in absence of excessive of alcohol consumption. Non Alcoholic Fatty Liver Disease ranges from simple steatosis to Nonalcoholic steatohepatitis and cirrhosis. Most cases (90%) of Non Alcoholic Fatty Liver Disease have simple steatosis with benign prognosis. Ten to thirty percent of Non -Alcoholic Fatty Liver Disease progresses to NASH and 25-40% of Nonalcoholic steatohepatitis undergoes progressive liver fibrosis.Ultimately 20-30% of Nonalcoholic steatohepatitis will go into cirrhosis during their lifetime. Nonalcoholic steatohepatitis cirrhosis has higher chances of (2.6% per year) going into hepatocellular carcinoma. There are several risk factors noted for Non Alcoholic Fatty Liver Disease. Some of which includes increasing age, metabolic syndrome, dietary factors etc. Investigations regarding liver function test can be divided into invasive and noninvasive types. Under invasive procedures comes liver biopsy and non-invasive includes radiological tests and various biochemical tests. This article tries to analyze different scoring systems and their significance in diagnosing steatohepatitis and fibrosis.